INNOVATION CONSTITUENT OF SUSTAINABLE DEVELOPMENT - O. Zhylinska; I. Orobets (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper substantiates an innovation constituent of sustainable development along with environmental, social and economic pillars of the concept. Determining of implementation details of innovation activity by J. Schumpeter is a theoretical prerequisite to understanding of innovation constituent. An innovator-entrepreneur provides a customer with an information image of 'new combinations.' The image is created by identifying customer's future needs, which outline business aims, subject and appropriate means for creating the innovation products. However, consumer choice is largely motivated by values and specific rules of behavior. The rules of consumer society that in the industrial age become the motive, morality and institution, did not consider the reproductive capabilities of the environment. This disagreement was previously presented in The Limits to Growth by the Club of Rome and was reflected in the concept of sustainable development, which gained immense significance after the report of the World Commission on Environment and Development in 1987 (Our Common Future). The study highlights importance for establishment of new social values that motivate innovators to change their thinking, comprehend their responsibility not only to consumers but also to the environment and future generations. The Rio+20 Corporate Sustainability Forum: Innovation and Collaboration for the Future We want, organized by the UN Global Compact, demonstrates the interest of entrepreneurs in practical implementation of the concept of sustainable development, through an effective innovation activity. The paper summarizes management tools for implementing business commitments to action in priority areas of ensuring sustainable development: Energy & Climate, Water & Ecosystems, Agriculture & Food, Economics & Finance of Sustainable Development, Social Development, and Urbanization & Cities. Main stages of changes in companies are outlined for making responsible innovation solutions and implementing the innovation constituent of sustainable development.